1998
DOI: 10.1159/000011886
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large Cell Lymphomas: Identification of Prognostic Factors and Validation of the International Non-Hodgkin’s Lymphoma Prognostic Index

Abstract: Several clinical prognostic factors have been identified that predict treatment outcome in patients with diffuse large cell lymphomas. An International Non-Hodgkin’s Lymphoma Prognostic Index (IPI) has been recently formulated. We tried to identify the clinical prognostic factors that predict treatment outcome in Greek patients with diffuse large cell lymphomas and validated the IPI in these patients. The possible prognostic variables for tumor response, relapse-free (RFS) and overall survival (OS) were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
0
31
0
2
Order By: Relevance
“…Elevated levels of LDH are considered a negative prognostic factor in many solid tumors, including advanced NPC, and have been associated with large tumor burden, tumor extension and high risk of metastasis [21-25]. Serum LDH levels twice normal levels are rarely seen in loco-regional disease but are commonly observed in NPC patients with liver metastasis or multiple organ metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of LDH are considered a negative prognostic factor in many solid tumors, including advanced NPC, and have been associated with large tumor burden, tumor extension and high risk of metastasis [21-25]. Serum LDH levels twice normal levels are rarely seen in loco-regional disease but are commonly observed in NPC patients with liver metastasis or multiple organ metastases.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the international prognostic index (IPI) [3], based on pre-treatment clinical data, for NHLs has enabled clinicians to successfully manage several highgrade NHLs. The IPI has also proven valid for specifi c adult cancers [4][5][6] but not yet for paediatric cancers. Prognostic indices at the genetic, molecular, biochemical, clinical, demographic and/or socioeconomic level [7] are being proposed and used for specifi c cancers [8], but not without confl icting results [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The IPI has also proven valid for specifi c adult cancers [4][5][6] but not yet for paediatric cancers. Prognostic indices at the genetic, molecular, biochemical, clinical, demographic and/or socioeconomic level [7] are being proposed and used for specifi c cancers [8], but not without confl icting results [5][6][7][8][9]. This study, while acknowledging its limitations, addresses this issue in comparison to reported literature on prognostic indices for paediatric NHL [9].…”
Section: Introductionmentioning
confidence: 99%
“…63,64 Extent of disease is determined by physical examination, followed by a thorough staging evaluation including CBC and evaluation of peripheral smear, serum chemistries, CXR or chest CT scan, abdominal and pelvic CT scan, and bone marrow studies. Serum lactate dehydrogenase (LDH), a marker for tumor load, 65 is monitored as well. Local radiation therapy following a negative staging evaluation should be considered in patients with CBPL in which a combination of clinical picture, histologic, immunohistologic, and/or clonality studies show features which may be considered worrisome 22 for potential progression to lymphoma.…”
Section: Discussionmentioning
confidence: 99%